2007
DOI: 10.1152/japplphysiol.01305.2006
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol replacement reverses ovariectomy-induced muscle contractile and myosin dysfunction in mature female mice

Abstract: Skeletal muscle contractility and myosin function decline following ovariectomy in mature female mice. In the present study we tested the hypothesis that estradiol replacement can reverse those declines. Four-month-old female C57BL/6 mice (n = 69) were ovariectomized (OVX) or sham operated. Some mice were treated immediately with placebo or 17beta-estradiol (OVX + E(2)) while other mice were treated 30 days postsurgery. Thirty or sixty days postsurgery, soleus muscles were assessed in vitro for contractile fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
162
4
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(193 citation statements)
references
References 34 publications
19
162
4
8
Order By: Relevance
“…The combination of NADH enzyme for aerobic oxidative metabolism reaction and myofibrillary ATPase histochemistry showed that the diameter and cross-sectional area of FOG and FG fibers were unaltered irrespective of food supplements or duration of their administration in mature female rat. Our results are in agreement with Moran et al (2007) who found, that the cross-sectional areas of all fiber types were not affected by estrogen status in mature female rodents. We rarely observed slow oxidative fibers across the samples, as also found in MG by Armstrong & Phelps (1984).…”
Section: Analyses Of Musclesupporting
confidence: 94%
See 2 more Smart Citations
“…The combination of NADH enzyme for aerobic oxidative metabolism reaction and myofibrillary ATPase histochemistry showed that the diameter and cross-sectional area of FOG and FG fibers were unaltered irrespective of food supplements or duration of their administration in mature female rat. Our results are in agreement with Moran et al (2007) who found, that the cross-sectional areas of all fiber types were not affected by estrogen status in mature female rodents. We rarely observed slow oxidative fibers across the samples, as also found in MG by Armstrong & Phelps (1984).…”
Section: Analyses Of Musclesupporting
confidence: 94%
“…Significant changes in physical activity and Table 3 Qualitative analyses of tibia fracture healing in osteoporotic rats exposed either to soy free (SF), daidzein (D), 4-methylbenzylidene camphor (4-MBC) or estradiol-17b-benzoate (E 2 ) supplemented diet up to 36 and 72 days post-fracture determined using fluorochromelabeled sections according to the plate side, opposite side, and endosteally metabolism in Ovx rats, discussed above are responsible for the increase in adipose tissues and the BW, consequently. In other studies, increased wet muscle mass in Ovx versus estrogen replaced adult female rodents was explained by an extracellular fluid accumulation because the cross-sectional area of all fiber types was not affected by estrogen status (McClung et al 2006, Moran et al 2007. In a previous study, it was stated that estrogen replacement in Ovx rats benefited atrophied muscle recovery from disuse atrophy (Kawano et al 1997).…”
Section: Analyses Of Musclementioning
confidence: 94%
See 1 more Smart Citation
“…Besides changes in the calcium mechanism, E2 can induce changes in the myosin filaments. Specifically, reduction in strong-binding structural state of myosin head leading to reduction in force has been reported in ovariectomized mice, while this effect is reversed in the presence of E2 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial function and the response to oxidative stress can be strongly affected by fiber composition (Anderson & Neufer 2006, Picard et al 2008, 2012. Ovariectomy has been reported to modify muscle contractile properties, phenotype, metabolism, and force-generating capacity (Moran et al 2006, Liu et al 2009c, whereas estradiol replacement reverses these alterations (Moran et al 2007, Liu et al 2009b, Cavalcanti-de-Albuquerque et al 2014. In this sense, it is not possible to rule out the hypothesis that the changes observed in white gastrocnemius mitochondrial function and oxidative stress response from OVX and OVXCE 2 rats are mediated by a change in fiber metabolism or phenotype; further studies would be necessary.…”
Section: Discussionmentioning
confidence: 99%